The Effect of The Example Non-Example Learning Model on The Learning Outcomes Of Grade IV Students In Science Learning - Hendrik Dunan Harianja; Lisbet Novianti Sihombing; Eva Pasaribu (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to determine: The Effect of Example Non Example Learning Model on the Learning Outcomes of Class IV Students in Science Learning at UPTD SD Negeri 091273 Pematangsiantar Academic Year 2025/2026. The type of research used in this study is quantitative research, which states that quantitative research is research in the form of numbers and its analysis uses statistics. The research design used is an experiment using the "one group pretest posttest design" design. The sample in this study were 25 class IV students of UPTD SD Negeri 091273. The instrument used in this study was in the form of multiple choice questions. The results of the research hypothesis testing are that there is a significant influence on this study from the data that has been tested, the data can be seen from the data analysis obtained the average results of the experimental class in the pre-test (50.48) and post-test (88.36). Based on the analysis of the pretest and posttest data, it shows that the sig value (2-tailed) is 0.00 <0.05, which is rejected and accepted. So it can be concluded that there is a significant influence on improving the learning outcomes of students who use the example non-example learning model on the learning outcomes of class IV students in science learning at UPTD SD Negeri 091273 Karang bangun Academic Year 2025/2026.